Answer:
x= 0 ,
,
![(-1)/(12)](https://img.qammunity.org/2020/formulas/mathematics/high-school/nrl4s7ev868nfucit3n7p6hornqjwpch9z.png)
Explanation:
Given, equation is
+
=
. →→→ (1)
Now, by cubing the equation on both sides, we get
(
+
)³ = (
)³
⇒ (15x-1) + (13x+1) + 3×
×
(
+
) = 64 x.
⇒ 28x + 3×
×
(
) = 64x.
(since from (1),
+
=
)
⇒ 12×
×
(
)= 36x.
⇒ 3x =
.
Now, once again cubing on both sides, we get
(3x)³ = (
)³.
⇒ 27x³ = (15x-1)(13x+1)(x).
⇒ 27x³ = 195x³ + 2x² - x
⇒ 168x³ + 2x² - x = 0
⇒ x(168x² + 2x -1) = 0
⇒ by, solving the equation we get ,
x = 0 ; x =
; x =
![(-1)/(12)](https://img.qammunity.org/2020/formulas/mathematics/high-school/nrl4s7ev868nfucit3n7p6hornqjwpch9z.png)
therefore, solution is x= 0 ,
,
![(-1)/(12)](https://img.qammunity.org/2020/formulas/mathematics/high-school/nrl4s7ev868nfucit3n7p6hornqjwpch9z.png)